Evidence of Neanderthals in the Balkans: The infant radius from Kozarnika Cave (Bulgaria). Issue 111 (October 2017) - Tillier, Anne-marie; Sirakov, Nikolay; Guadelli, Aleta; Fernandez, Philippe; Sirakova, Svoboda; Dimitrova, Irena; Ferrier, Catherine; Guérin, Guillaume; Heidari, Maryam; Krumov, Ivailo; Leblanc, Jean-Claude; Miteva, Viviana; et al.
Abstract: Excavations conducted by a Bulgarian-French team at Kozarnika Cave (Balkans, Bulgaria) during several seasons yielded a long Paleolithic archaeological sequence and led to the discovery of important faunal, lithic, and human samples. This paper aims to describe the unpublished radius shaft of an infant who died approximately before the sixth month postnatal that was recovered from layer 10b, which contained East Balkan Levallois Mousterian with bifacial leaf points. The layer was dated between 130 and 200 ka (large mammals biochronology) and between 128 ± 13 ka and 183 ± 14 ka (OSL), i.e. OIS6. Here we show that, given the scarcity of Middle Pleistocene infant remains in general, and Middle Paleolithic human remains from this part of Eastern Europe in particular, the study of the Kozarnika specimen is of special interest. We discuss its place in the Middle Pleistocene European hominine record and substantiate the hypothesis of early Neanderthal presence in the eastern Balkans.